B Lymphocytes as Targets of the Immunomodulatory Properties of Human Amniotic Mesenchymal Stromal Cells - Magatti, Marta; Masserdotti, Alice; Bonassi Signoroni, Patrizia; Vertua, Elsa; Stefani, Francesca Romana; Silini, Antonietta Rosa; Parolini, Ornella (Frontiers in Immunology, 2020)
Mesenchymal stromal cells (MSC) from the amniotic membrane of human term placenta (hAMSC), and the conditioned medium generated from their culture (CM-hAMSC) offer significant tools for their use in regenerative medicine mainly due to their immunomodulatory properties. Interestingly, hAMSC and their CM have been successfully exploited in preclinical disease models of inflammatory and autoimmune diseases where depletion or modulation of B cells have been indicated as an effective treatment, such as inflammatory bowel disease, lung fibrosis, would healing, collagen-induced arthritis, and multiple sclerosis. While the interactions between hAMSC or CM-hAMSC and T lymphocytes, monocytes, dendritic cells, and macrophages has been extensively explored, how they affect B lymphocytes remains unclear. Considering that B cells are key players in the adaptive immune response and are a central component of different diseases, in this study we investigated the in vitro properties of hAMSC and CM-hAMSC on B cells. We provide evidence that both hAMSC and CM-hAMSC strongly suppressed CpG-activated B-cell proliferation. Moreover, CM-hAMSC blocked B-cell differentiation, with an increase of the proportion of mature B cells, and a reduction of antibody secreting cells formation. We observed the strong inhibition of B cell terminal differentiation into CD138+ plasma cells, as further shown by a significant decrease of the expression of interferon regulatory factor 4 (IRF-4), PR/SET domain 1(PRDM1), and X-box binding protein 1 (XBP-1) genes. Our results point out that the mechanism by which CM-hAMSC impact B cell proliferation and differentiation is mediated by secreted factors, and prostanoids are partially involved in these actions. Factors contained in the CM-hAMSC decreased the CpG-uptake sensors (CD205, CD14 and TLR9), suggesting that B cell stimulation was affected early on. CM-hAMSC also decreased the expression of interleukin-1 receptor-associated kinase (IRAK)-4, consequently inhibiting the entire CpG-induced downstream signaling pathway. Overall, these findings add insight into the mechanism of action of hAMSC and CM-hAMSC and are useful to better design their potential therapeutic application in B-cell mediated diseases.